2023
DOI: 10.3389/fpls.2023.1196765
|View full text |Cite
|
Sign up to set email alerts
|

Fungal strain and crop cultivar affect growth of sweet pepper plants after root inoculation with entomopathogenic fungi

Liesbet Wilberts,
Nicolas Rojas-Preciado,
Hans Jacquemyn
et al.

Abstract: As endophytes, entomopathogenic fungi can protect plants against biotic and abiotic stresses and at the same time promote plant growth and plant health. To date, most studies have investigated whether Beauveria bassiana can enhance plant growth and plant health, while only little is known about other entomopathogenic fungi. In this study, we evaluated whether root inoculation of the entomopathogenic fungi Akanthomyces muscarius ARSEF 5128, B. bassiana ARSEF 3097 and Cordyceps fumosorosea ARSEF 3682 can promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…In contrast to Wilberts et al ., 26 the fungus could not be detected at the end of the experiments, suggesting that endophytic colonization was either transient or that the fungus did not colonize the plant systematically, at least not in the analyzed leaves (fifth leaf). Although the reasons for this discrepancy are still unclear, our results are consistent with a recent study which showed that A. muscarius ARSEF 5128 enhances plant growth, while it was also not detected at the end of the experiments 52 . Colonization of plant tissue by entomopathogenic fungi is often found to be transient after artificial inoculation, especially when plants are grown in nonsterile soil, as in this study 53–55 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast to Wilberts et al ., 26 the fungus could not be detected at the end of the experiments, suggesting that endophytic colonization was either transient or that the fungus did not colonize the plant systematically, at least not in the analyzed leaves (fifth leaf). Although the reasons for this discrepancy are still unclear, our results are consistent with a recent study which showed that A. muscarius ARSEF 5128 enhances plant growth, while it was also not detected at the end of the experiments 52 . Colonization of plant tissue by entomopathogenic fungi is often found to be transient after artificial inoculation, especially when plants are grown in nonsterile soil, as in this study 53–55 .…”
Section: Discussionsupporting
confidence: 87%
“…Many factors may affect the degree to which entomopathogenic fungi colonize plant tissue, including inoculation method, environmental conditions and competing microorganisms in the rhizosphere or endopshere 56–58 . Nevertheless, despite limited or even no long‐term endophytic colonization, entomopathogenic fungi have been found to promote plant growth or enhance plant defenses against herbivores, suggesting that long‐term colonization or systemic colonization is not required to elicit positive fungus‐mediated effects 21,35,52,56,59,60 . However, further research is needed to find out to what extent fungal colonization degree affects the plant phenotype and its interaction with higher trophic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma harzianum T22 is primarily known to colonize plant roots epiphytically but has also been found to colonize plant tissues endophytically ( Harman et al., 2004 ). The three selected strains have been found to offer plants various benefits, including enhanced plant growth ( Sani et al., 2020 ; Van Hee et al., 2023 ; Wilberts et al., 2023 ) and increased resistance against pathogens and/or herbivorous insects ( Jaber and Alananbeh, 2018 ; Jaber and Araj, 2018 ; Alınç et al., 2021 ; Wilberts et al., 2022 ; Meesters et al., 2023 ; Van Hee et al., 2023 ). The fungal strains were preserved on potato dextrose agar (PDA) plugs in 35% glycerol at -80°C until further use.…”
Section: Methodsmentioning
confidence: 99%
“…Volatile analysis revealed a total of 75 compounds in the headspace of sweet pepper plants subjected to the different treatments (S1 Table and S1 Fig). These compounds belonged to the class of terpenoids (52), nitrogen-containing compounds (3), fatty acid derivatives (7), and benzenoids or phenylpropanoids (13) (S1 Table ). PerMANOVA did not indicate any statistical differences in VOC composition between the different treatments when considering all data together (F 6,59 = 1.462, P = 0.055).…”
Section: Volatile Compositionmentioning
confidence: 99%
“…Most plants live in close association with diverse microorganisms, including bacteria and fungi, several of which play a crucial role in the interactions between plants and insect herbivores [4,5]. Plant-beneficial microorganisms like mycorrhizal fungi, plant-growth promoting rhizobacteria or plant-growth promoting fungi not only enhance plant growth [6][7][8], but also protect plants against herbivores through direct and indirect mechanisms [9][10][11][12][13]. Direct effects may result from the production of deterrents, antifeedants or toxins, exerting direct negative effects on the behaviour or performance of the herbivorous insects [14,15].…”
Section: Introductionmentioning
confidence: 99%